(untitled) (Revista Latino-Americana de Enfermagem, 2012)
PURPOSE: This study has described and analysed the functional independence of the patients served in the haemodialysis services of a countryside town in the State of São Paulo, Brazil, using the Functional Independence Measure (FIM). METHOD: The population considered was that of 214 patients being treated with haemodialysis, assessed in 2011, by means of a social, demographic and clinical report, a Mini-Mental State Examination (MMSE) and also the FIM. RESULTS: The mean age of the population under study was 58.01 years, while the mean FIM point score was 118.38 points, showing a level of complete or modified independence within this population. Even though the level of dependence found has been low, this can be highlighted, within the locomotion domain, in the activity of going up and down stairs (10.28%). Age, complications arising from haemodialysis, and comorbidities show a negative correlation with FIM. CONCLUSION: Awareness of the level of functional independence of the patients being subjected to treatment with haemodialysis is essential in order to back up intervention for the improvement of nursing assistance provided to this population.